Limitations of a Purely Salvation-historical Approach to Biblical Theology - Lockett, Darian R. (Horizons in biblical theology, 2017)
A salvation-historical approach to biblical theology emphasizes the historical and progressive nature of revelation such that the Bible’s primary meaning is (too often) reduced to its reference to the sequential events of a special (salvation) history. After offering a general description of the development of the salvation-historical approach to biblical theology, the essay considers the representative example of D. A. Carson. Then, noting the criticisms of Hans Frei, Karl Barth, and Brevard Childs, the paper argues that limiting one’s biblical theology to a salvation-historical approach replaces Christ as the subject matter of both Testaments with “the temporally distinct and ordered stages of the history of salvation.” Although the insights of a redemptive-historical biblical theology are important, when taken as the exclusive methodology for biblical theology it risks flattening the relationship between the two Testaments and missing Scripture’s theological subject matter.